2003
DOI: 10.1111/j.1572-0241.2003.07584.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a Helicobacter pylori treatment strategy on health care expenditures in patients with peptic ulcer disease and dyspepsia

Abstract: Treatment of H. pylori for patients with chronic dyspepsia or self-reported peptic ulcer does not reduce expenditures over 1 yr of follow up. H. pylori treatment for patients chronically receiving acid suppressive treatment with a prior documented ulcer significantly reduces expenditures if GERD and Barrett's esophagus are absent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…There was no corresponding decrease in IM prevalence. Instead IM prevalence in 2002-2003 was significantly higher than the prevalence in previous few years (P = 0.04). Conclusion: The prevalence of IM did not change in the period from 1998 to 2003 despite a drop in the prevalence of Hp infection since 1994.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…There was no corresponding decrease in IM prevalence. Instead IM prevalence in 2002-2003 was significantly higher than the prevalence in previous few years (P = 0.04). Conclusion: The prevalence of IM did not change in the period from 1998 to 2003 despite a drop in the prevalence of Hp infection since 1994.…”
mentioning
confidence: 65%
“…However, the incidence of gastric ulcer and gastric cancer did not follow a similar trend. 12,13 The study period may be too short to detect the change or the timing of H. pylori eradication in those affected individuals is not early enough to prevent the precancerous lesions, and hence gastric cancer. Since the incidence of gastric cancer and the prevalence of intestinal metaplasia were shown to go in a similar trend and course, 14 a drop in the incidence of gastric cancer can only be expected if there is a drop in the prevalence of intestinal metaplasia.…”
Section: Introductionmentioning
confidence: 99%
“…The most effective therapy for H. pyloriassociated ulcer disease is bacterial eradication. A recent study confirmed that patients on acid suppressive maintenance therapy for documented peptic ulcer disease benefited from H. pylori eradication, which approach was cost-effective and enabled withdrawal of acid suppression in many patients [4]. H. pylori eradication did not however, lead to any cost savings or reduction in the maintenance use of acid suppressants in patients with a self-reported, nondocumented Correspondence: Ernst J. Kuipers, Department of Gastroenterology and Hepatology, Erasmus MC University Medical Center, PO Box 2040, 3000 CA Rotterdam, the Netherlands.…”
Section: Peptic Ulcer Diseasementioning
confidence: 91%